Educational Inequality and Intergenerational Mobility in Latin America: A New Database - Neidhoefer, Guido (2017)
Causes and consequences of the intergenerational persistence of inequality are a topic of great interest among different fields in economics. However, issues of data availability have restricted a broader and cross-national perspective on the topic so far. Based on rich sets of harmonized household survey data, we contribute to fill this gap providing time series for several indexes of relative and absolute intergenerational education mobility for 18 Latin American countries over 50 years. In this paper, we introduce this new database and describe the observed patterns. We find that on average intergenerational mobility has been rising in Latin America. This pattern seems to be driven by high upward mobility of children from low-educated families, while there is substantial immobility at the top of the distribution. Significant cross-country differences can be observed which are associated with the degree of income inequality, poverty, economic growth and public educational expenditures.